High-precision patterning method of perovskite thin film and application
Patent Information
- Application Number
- CN202411175347.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-26
AI Technical Summary
The prior art is difficult to achieve high-precision and high-resolution perovskite film patterning, especially when fluorescent materials are sensitive to short-wavelength light, and traditional photolithography and nanoimprinting techniques have problems with template deformation and repeatability. .
Femtosecond laser direct writing technology combined with high-quality polymer matrix to wrap perovskite films, through the ultra-high peak intensity and nonlinear multi-photon absorption of femtosecond laser, high-precision patterning with a minimum feature size of 80nm is achieved, avoiding optics Diffraction limit and improve stability by isolating water-oxygen contact by polymer.
It realizes micro and nano-scale patterning with high precision and clear edges, broadens the application of perovskites in the fields of high-resolution display, anti-counterfeiting and encryption, and the patterned film maintains an original luminous intensity of more than 90% under harsh conditions.
Smart Images

Figure CN119141001A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of patterning technology, and in particular to a high-precision patterning method and application of a perovskite film. Background Art
[0002] Metal halide perovskites are considered to be ideal candidate materials for the next generation of optoelectronic devices due to their excellent optoelectronic properties and strong cost-effectiveness. They have achieved excellent scientific research results and have been gradually applied in the fields of solar cells, light-emitting diodes, photodetectors and advanced anti-counterfeiting. As fluorescent materials, perovskites have tunable emission wavelengths, high photoluminescence quantum yields, high color purity and low-cost processing technology, making them ideal materials for information storage, encryption and anti-counterfeiting applications.
[0003] In the process of preparing perovskite materials into optoelectronic devices, patterning and arraying are crucial links. By constructing orderly patterns and writing specific information, special properties can be given to materials, such as integrated photodetector arrays for image sensing and LED arrays for display. Whether high-precision and high-quality patterned films can be prepared determines whether the corresponding high-quality applications can be realized. Therefore, improving the quality of patterned films is a key step in improving device performance and broadening the application field of perovskite materials. Considering the integration and miniaturization of system applications, micro / nanoscale patterned perovskites can store more information at the same size, promoting applications with higher integration. Therefore, it is critical to develop a new technology for stably achieving high-resolution patterned perovskites. Inkjet printing is a maskless patterning technology that has been widely studied to achieve high-quality patterned perovskite films. However, due to the influence of nozzle size and ink rheological properties, the pixel size is limited to less than 5μm. Photolithography patterning is a precision perovskite patterning technology, but when the material is exposed to traditional photolithography solvents, it will have a negative impact on its performance, which seriously limits the development of perovskite-based devices. Nanoimprinting technology has the advantages of high precision, high efficiency and low cost. It is the most promising technology for micro-nanostructure preparation to replace photolithography. However, the nanoimprinting method has the problem of template deformation during the imprinting process, which seriously affects the repeatability and fidelity of the imprinting.
[0004] Compared with the above-mentioned commonly used patterning methods, the emerging femtosecond laser processing provides high energy in a limited area through a non-mechanical contact process, and has been proven to have the function of realizing programmed ablation and flexible removal of various materials, and can do so without destroying the existing structure on the substrate, which is beneficial to the development of multi-component devices. In addition, due to the ultra-short pulse of the femtosecond laser, the ablation or thermal vaporization caused by the induced material ionization, lattice melting and Coulomb explosion only occurs within a few picoseconds, which is much shorter than the material thermal diffusion time (nanosecond scale), which can minimize the impact on the surrounding materials, make the ablation pattern have high precision and clear edges, and have the advantages of high efficiency and good controllability.
[0005] To date, femtosecond laser direct writing has been proven to be an effective technology for fine processing and engineering of material microstructures in time and space. Dong et al. reported a three-dimensional (3D) patterning technology for femtosecond laser printing of perovskite quantum dots, which successfully achieved the reversible in-situ formation and decomposition of perovskite in a glass matrix. The patterning diameter of the laser irradiation area can be increased from 30μm to 65μm by adjusting the laser power density or extending the exposure time. However, the patterning of quantum dots inside the glass requires high excitation power and additional heating, which is challenging for industrial applications (see Nat. Photonics 14, 82-88 (2020)). Gan et al. used the nonlinear absorption and energy deposition induced by femtosecond lasers to control the focusing position of the laser in the precursor solution, and could form laser-processed nanocomposites of arbitrary shapes on the micrometer scale, with a minimum line width of 1.2μm (see J. Mater. Chem. C 8, 3409-3417 (2020)). Although femtosecond laser direct writing has been demonstrated to be a sub-diffraction imaging technique, the resolution of direct writing is still affected by the Airy disk diameter (1.22λ / NA, where λ and NA are the wavelength and numerical aperture of the objective lens, respectively). Obviously, a shorter laser wavelength or a larger numerical aperture is conducive to improving resolution, but fluorescent materials such as perovskites are more sensitive to short-wavelength light, and the numerical aperture of the objective lens cannot be increased infinitely. Therefore, femtosecond laser direct writing high-resolution patterning technology for fluorescent materials is still a huge challenge.
[0006] In summary, it is critical to develop a new technology for efficient, stable and high-precision patterning of perovskite films. Summary of the invention
[0007] In view of the defects and deficiencies in the above-mentioned prior art, the present invention provides a high-precision patterning method suitable for perovskite films to broaden the application of perovskite in the fields of high-resolution display, anti-counterfeiting or encryption. The present invention utilizes the ultra-high peak intensity of femtosecond lasers, combined with the digital processing characteristics of laser direct writing systems, to achieve high-precision laser ablation patterning in designated areas on perovskite films, and can achieve a minimum feature size of 80nm, which is approximately λ / 10 of the exposure source, breaking the optical diffraction limit, which is not achievable with other patterning technologies. In addition, the patterned perovskite film prepared by the present invention has excellent water-oxygen stability, and can maintain more than 90% of the original luminous intensity after being stored for 120 days under laboratory conditions, and can be used for a long time in integrated devices even under harsh conditions.
[0008] The femtosecond laser direct writing perovskite of the present invention has several significant characteristics: first, the femtosecond laser pulse width is extremely short, at the femtosecond level (10 -15s), and the energy density of femtosecond laser after focusing can reach 10 14 -10 15 W / cm 2 The electric field strength can reach 10 10 V / cm; secondly, due to the addition of high mass fraction polymers, such as PMMA, in the perovskite film, compared with the thermal conductivity of perovskite CsPbI3 (0.45±0.05W / mK), PMMA has a low thermal conductivity of 0.14±0.2W / mK, which can accurately control the laser ablation points to obtain higher resolution patterns; thirdly, the perovskite film has no absorption in the selected 700-1080nm femtosecond laser band, and nonlinear multiphoton absorption occurs in the laser direct writing process, that is, when the laser intensity is close to the ablation threshold, the narrower and steeper the effective intensity curve of the spot is, by precisely controlling the laser intensity, only a small part of the focused spot exceeds the perovskite ablation threshold, so that the feature size exceeds the optical diffraction limit; fourthly, the preparation method of using a polymer matrix to wrap the perovskite can obtain a thin film with high flatness and uniformity, and there are no obvious holes or cracks on the film surface, which is suitable for high-precision laser direct writing, and the polymer can effectively isolate the perovskite from water and oxygen, which is beneficial to improve stability.
[0009] An object of the present invention is to provide a high-precision patterning method for a perovskite film, the high-precision patterning method for a perovskite film comprising the following steps:
[0010] S1, adding a polymer and a perovskite precursor into a solvent, heating and stirring, to obtain a perovskite precursor solution;
[0011] S2, coating the perovskite precursor solution on a substrate to obtain a perovskite precursor film;
[0012] S3, annealing the perovskite precursor film to obtain a perovskite film;
[0013] S4, processing the perovskite film using a femtosecond laser direct writing technique to obtain a high-precision patterned perovskite film;
[0014] in,
[0015] The perovskite is a nanocrystalline perovskite;
[0016] In the perovskite film, the mass fraction of the polymer is 70-90%;
[0017] The wavelength of the femtosecond laser is 700-1080nm;
[0018] In the light spot formed by the femtosecond laser, the energy of the femtosecond laser presents a Gaussian distribution curve from the center to the periphery of the light spot, the peak energy of the Gaussian distribution curve reaches 200mW, and the energy decreases from the middle to both sides of the Gaussian distribution curve.
[0019] Furthermore, the pulse width of the femtosecond laser is 50-200fs.
[0020] Furthermore, the power of the femtosecond laser is 0.1-200 mW.
[0021] Furthermore, the spot diameter of the laser is 0.5-50 μm.
[0022] Furthermore, the polymer is selected from one or more of polyvinylidene fluoride, polymethyl methacrylate, polyvinyl acetate, cellulose acetate, polysulfone, polyamide, polyimide, polycarbonate, polystyrene, polyvinyl chloride, polyvinyl alcohol, ABS plastic or polyacrylonitrile; the polymer is a transparent resin matrix, and the perovskite is distributed in the transparent resin matrix; specifically, the transparent resin matrix is a transparent material dissolved in a polar solvent of dimethylformamide, dimethylacetamide, N-methylpyrrolidone or dimethyl sulfoxide.
[0023] Furthermore, the perovskite precursor solution is a uniform, viscous, transparent solution, wherein the polymer and the perovskite precursor are completely dissolved; the mass fraction of the polymer is 1-50%, and the mass concentration of the perovskite precursor is 5-10%.
[0024] Further, in the perovskite film, the molecular formula of the perovskite is ABX3;
[0025] in,
[0026] A is selected from Cs + 、CH3NH 3+ or CH5N 2+ One or more of;
[0027] B is selected from one or more of In, Ag, Al, Ti, Ge, Sn, Pb, Sb, Bi, Cu or Mn;
[0028] X is selected from Cl - Br - or I - One or more of .
[0029] Furthermore, the thermal conductivity of the perovskite is 0.4-10 W / mK; the thermal conductivity of the polymer is 0.1-0.5 W / mK.
[0030] Furthermore, the perovskite film is a flat and uniform polymer-wrapped perovskite film, and its molecular formula is CsPbCl m Br 3-m and CsPbBr m I 3-m , where the value range of m is 0≤m≤3.
[0031] Furthermore, in step S1, the heating temperature is 50-90°C; and the stirring time is 1-5h.
[0032] Furthermore, in step S3, the annealing temperature is 60-90° C. and the time is 10-30 min.
[0033] Furthermore, the thickness of the perovskite film is 0.01-500 μm.
[0034] Furthermore, in step S4, ablation or thermal vaporization caused by material ionization, lattice melting and Coulomb explosion will occur in the laser irradiation area, achieving ablation removal of the perovskite film, thereby obtaining a micro pattern. Femtosecond laser precision engineering has the advantages of large area, high throughput, and far-field nano-processing. Focusing on the perovskite film can achieve simple and reliable pattern ablation.
[0035] Another object of the present invention is to provide the application of the high-precision patterning method of the above-mentioned perovskite film in the fields of high-resolution display, anti-counterfeiting or encryption.
[0036] The present invention has the following beneficial effects:
[0037] (1) The present invention proposes a simple femtosecond laser direct writing method to prepare high-precision patterned perovskite films. There is an iceberg effect in the interaction between femtosecond laser and nanocrystalline perovskite: when the laser intensity is close to the ablation threshold, the iceberg effect is highly nonlinearly related to the femtosecond laser intensity, that is, the more photons are absorbed simultaneously, the narrower and steeper the effective intensity curve of the spot is. The present invention precisely controls the laser intensity so that only a small part of the focused spot exceeds the perovskite ablation threshold, thereby making the feature size exceed the optical diffraction limit and reach λ / 10 of the exposure source, with a minimum line width of 80nm. Due to the ultrashort pulse of the femtosecond laser, the induced ablation phenomenon only occurs within a few picoseconds, which is much shorter than the thermal diffusion time of the material (nanosecond scale). At the same time, based on the difference in thermal conductivity between perovskite and polymer, the laser ablation range can be precisely controlled to minimize the impact on surrounding materials, so that the pattern has high precision and clear edges, and can complete the preparation of high-quality micro- and nano-scale patterns.
[0038] (2) Compared with traditional patterning methods, the present invention can accurately and efficiently obtain high-precision fluorescent patterned films in designated areas without the need for a vacuum environment, a template, or complex post-processing. Since nanoscale patterns can store more information at the same size, it promotes applications with higher integration. The patterning technology proposed in the present invention provides a promising manufacturing candidate for data storage, anti-counterfeiting, and high-security information encryption.
[0039] (3) Sensitivity to environmental factors such as oxygen and humidity has always been one of the obstacles to the practical application of perovskites. The present invention uses a polymer matrix to wrap perovskites to effectively isolate them from contact with water and oxygen. The resulting patterned perovskite film has excellent water-oxygen stability and is expected to be used for a long time even under harsh conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 A flow chart of preparing a high-precision patterned perovskite film in Example 1 is shown.
[0041] Figure 2 The transmission electron microscope image of the perovskite film prepared in Example 1 is shown.
[0042] Figure 3 The actual fluorescence emission image and absorption spectrum of the perovskite film prepared in Example 1 under ultraviolet excitation are shown.
[0043] Figure 4 The SEM image of the patterned perovskite film prepared in Example 1 with sub-diffraction feature size and the schematic diagram of the iceberg effect of the nonlinear absorption process are shown;
[0044] in,
[0045] Figure 4 (a) shows a SEM image of a patterned perovskite film prepared in Example 1 with sub-diffraction feature size;
[0046] Figure 4 (b) shows a schematic diagram of the iceberg effect in the nonlinear absorption process of the perovskite film prepared in Example 1.
[0047] Figure 5 The fluorescent images and SEM images of the patterned QR code, the logo of South China Normal University, and the Chinese element pattern of the perovskite film prepared in Example 1 under ultraviolet excitation are shown;
[0048] in,
[0049] Figure 5 (a) shows the patterned two-dimensional code under UV excitation and its SEM image;
[0050] Figure 5(b) shows the logo of South China Normal University and its SEM image under UV excitation;
[0051] Figure 5 (c) shows the fluorescence image of the Chinese element pattern under UV excitation and its SEM image.
[0052] Figure 6 The optical path diagram of the femtosecond laser patterning technology used in Example 2 is shown.
[0053] Figure 7 A planar SEM image of the perovskite film prepared in Example 2 is shown.
[0054] Figure 8 The fluorescence emission diagram of the perovskite film prepared in Example 2 under ultraviolet excitation is shown.
[0055] Fig. 9 The color gamut range achieved by the perovskite film prepared in Example 2 in the International Committee on Color (CIE) 1931 color coordinates and the comparison with the NTSC standard color gamut are shown.
[0056] Fig.10 The fluorescence image of the patterned words "South China Normal University" on the high-precision patterned perovskite film prepared in Example 2 under ultraviolet excitation is shown.
[0057] Fig.11 The photoluminescence (PL) intensity change of the perovskite film prepared in Example 2 under laboratory conditions is shown.
[0058] Fig.12 The photoluminescence (PL) intensity change of the perovskite film prepared in Example 2 in deionized water is shown.
[0059] Fig.13 A bright field microscope image of the perovskite film prepared in Comparative Example 2 is shown.
[0060] Fig.14 The fluorescence image of the patterned micro quick response code (QR code) of Application Example 1 under ultraviolet excitation is shown.
[0061] Fig.15 A schematic diagram showing the use of a smart phone, a portable ultraviolet lamp and a microscope to obtain the fluorescent micro-rapid response code and ACSII encrypted coding information in Application Examples 1 and 2 of the present invention.
[0062] Fig.16 The fluorescence image of the patterned binary 7-bit ASCII code of Application Example 2 under ultraviolet excitation is shown. DETAILED DESCRIPTION
[0063] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0064] Unless otherwise stated, the raw materials, reactions and post-treatment methods mentioned in the examples are common raw materials on the market and technical methods well known to those skilled in the art.
[0065] The average molecular weight of PMMA in the examples and comparative examples of the present invention is 120,000, and it was purchased from Beijing Bainowei Biotechnology.
[0066] The SEM test in the embodiments of the present invention and the comparative examples adopts the ZEISS Ultra 55 instrument / model.
[0067] The femtosecond laser in the embodiment of the present invention adopts the Coherent Chameleon instrument / model.
[0068] The fluorescence spectrum test in the embodiment of the present invention adopts the fluorescence spectrophotometer FL970 instrument / model.
[0069] The absorption spectrum test in the embodiment of the present invention adopts Lambd950 instrument / model.
[0070] Example 1
[0071] A high-precision patterning method for a perovskite film, the high-precision patterning method for a perovskite film comprising the following steps:
[0072] S1, add 0.5g PMMA, 0.1mmol PbI2, 0.1mmol CsI, and 0.05mmol OAI into 2.5ml DMF, heat and stir at 60℃ for 3h to obtain a perovskite precursor solution;
[0073] S2, drop coating the perovskite precursor solution onto a glass substrate, then placing the glass substrate on a coating machine, turning on a vacuum pump, and spin coating at a speed of 2600 r / min for 30 seconds to obtain a perovskite precursor film;
[0074] S3, transferring the perovskite precursor film to a 90° C. hot stage and thermally annealing for 10 min to obtain a perovskite film;
[0075] S4. Import the prepared pattern into the laser direct writing system, set the laser wavelength to 800nm, the pulse width to 200fs; the laser power to 64mW, and the spot diameter to 2μm; then place the perovskite film on a displacement platform, observe it through the CCD, and then adjust the height of the displacement platform to focus the femtosecond laser on the surface of the perovskite nanocrystalline film, and then start the patterning process. The femtosecond laser moves according to the set path. After completion, a high-precision patterned perovskite film is obtained, and the size of the pattern is 200×200μm 2 .
[0076] In this embodiment, the perovskite film is a PMMA-wrapped CsPbI3 perovskite nanocrystalline film, and both the luminescence peak and the absorption peak are located at 688 nm.
[0077] During the patterning process of this embodiment, the perovskite nanocrystals in the femtosecond laser irradiation area undergo ablation and thermal vaporization, and have obvious red fluorescence under dark field.
[0078] Figure 1 A flow chart of preparing a high-precision patterned perovskite film in Example 1 is shown; from left to right, the preparation of a perovskite precursor film and the preparation of a perovskite film are respectively shown.
[0079] Figure 2 The transmission electron microscope image of the perovskite film prepared in Example 1 is shown; Figure 2 It can be seen that the perovskite film prepared in Example 1 is a nanocrystalline film, the nanocrystals are coated with PMMA, and are evenly dispersed in the polymer matrix, with an average size of 13.7±1.4 nm.
[0080] Figure 3 The actual fluorescence emission image and absorption spectrum of the perovskite film prepared in Example 1 under ultraviolet excitation are shown.
[0081] Depend on Figure 3 It can be seen that the film has a PL peak with a half-width of 36nm (94meV) at 688nm, which corresponds to the exciton absorption peak at 688nm. In addition, the film has no absorption in the 800nm band. When writing information on the film using an 800nm femtosecond laser, nonlinear multiphoton absorption occurs. The inset shows the actual image of the film's fluorescence emission under UV excitation.
[0082] Figure 4 The SEM image of the patterned perovskite film prepared in Example 1 with sub-diffraction feature size and the schematic diagram of the iceberg effect of the nonlinear absorption process are shown;
[0083] in,
[0084] Figure 4(a) shows a SEM image of a patterned perovskite film prepared in Example 1 with sub-diffraction feature size;
[0085] Figure 4 (b) shows a schematic diagram of the iceberg effect in the nonlinear absorption process of the perovskite film prepared in Example 1.
[0086] Figure 5 The fluorescent images and SEM images of the patterned QR code, the logo of South China Normal University, and the Chinese element pattern of the perovskite film prepared in Example 1 under ultraviolet excitation are shown;
[0087] in,
[0088] Figure 5 (a) shows the patterned two-dimensional code under UV excitation and its SEM image;
[0089] Figure 5 (b) shows the logo of South China Normal University and its SEM image under UV excitation;
[0090] Figure 5 (c) shows the fluorescence image of the Chinese element pattern under UV excitation and its SEM image.
[0091] Example 2
[0092] A high-precision patterning method for a perovskite film, the high-precision patterning method for a perovskite film comprising the following steps:
[0093] S1, add 0.5g PMMA, PbX2, CsX, and AX into 2.5ml DMSO, heat and stir at 60℃ for 3h to obtain a perovskite precursor solution;
[0094] S2, drop coating the perovskite precursor solution onto a glass substrate, then placing the glass substrate on a coating machine, turning on a vacuum pump, and spin coating at a speed of 2600 r / min for 30 seconds to obtain a perovskite precursor film;
[0095] S3, transferring the perovskite precursor film to a 90° C. hot stage and thermally annealing for 10 min to obtain a perovskite film;
[0096] S4. Import the prepared pattern into the laser direct writing system, set the laser wavelength to 800nm, the pulse width to 200fs; the laser power to 70mW, and the spot diameter to 2μm; then place the perovskite film on a displacement platform, observe it through the CCD, and then adjust the height of the displacement platform to focus the femtosecond laser on the surface of the perovskite nanocrystalline film, and then start the patterning process. The femtosecond laser moves according to the set path. After completion, a high-precision patterned perovskite film is obtained, and the size of the pattern is 200×200μm2 ;
[0097] Wherein, in the perovskite precursor, X is selected from Cl, Cl m Br 3-m Br,Br m I 3-m , I, the value range of m is 0≤m≤3, as shown in Table 1.
[0098] Table 1 Selection and dosage of perovskite precursors and molecular formula of the prepared perovskite
[0099]
[0100]
[0101] In this embodiment, the perovskite film is a PMMA-wrapped CsPbX3 nanocrystalline perovskite film. By adjusting the ratio of halides, the luminescence peak of the multicolor film is located at 422-688nm.
[0102] During the patterning process of this embodiment, the perovskite nanocrystals in the femtosecond laser irradiation area undergo ablation and thermal vaporization, and exhibit obvious fluorescence under dark field.
[0103] Figure 6 The optical path diagram of the femtosecond laser patterning technology used in Example 2 is shown.
[0104] Figure 7 A planar SEM image of the perovskite film prepared in Example 2 is shown; Figure 7 It can be seen that the surface of the perovskite film is smooth, without obvious holes or cracks, and is suitable for high-precision femtosecond laser direct writing.
[0105] Figure 8 The fluorescence emission diagram of the perovskite film prepared in Example 2 under ultraviolet excitation is shown; Figure 8 It can be seen that the emission peak of CsPbCl3 is 422nm; the emission peak of CsPbClBr2 is 485nm; the emission peak of CsPbBr3 is 517nm; 2.5 I 0.5 The emission peak of CsPbBr2I is 542nm; the emission peak of CsPbBr2I is 580nm; the emission peak of CsPbBrI2 is 650nm; and the emission peak of CsPbI3 is 688nm.
[0106] Fig. 9 The color gamut range of the perovskite film prepared in Example 2 in the International Committee on Color (CIE) 1931 color coordinates and the comparison with the NTSC standard color gamut are shown; Fig. 9It can be seen that the multicolor perovskite film prepared and used in the present invention covers a wide color gamut and has broad application prospects in the display field.
[0107] Fig.10 The fluorescence image of the patterned words "South China Normal University" on the high-precision patterned perovskite film prepared in Example 2 under ultraviolet excitation is shown.
[0108] Fig.11 The photoluminescence (PL) intensity variation of the perovskite film prepared in Example 2 under laboratory conditions is shown; Fig.11 It can be seen that after 120 days, the luminescence intensity of the blue, green and red perovskite films remained at 93.84%, 94.19% and 90.77% of the initial intensity, respectively.
[0109] Fig.12 The photoluminescence (PL) intensity change of the perovskite film prepared in Example 2 in deionized water is shown; Fig.12 It can be seen that after being immersed in deionized water for 31 days, the three films still exhibited significant luminescence performance, and their luminescence intensity remained above 80% of the initial value.
[0110] Comparative Example 1
[0111] A high-precision patterning method for a perovskite film, the difference between this comparative example and Example 1 is that in step S3, the laser used is a continuous wave laser with a wavelength of 808nm, and the other components and preparation methods are the same as those in Example 1. Since the energy of the continuous wave laser is low, it is not enough to affect the perovskite film, and thus the ablation effect cannot be achieved.
[0112] Comparative Example 2
[0113] A high-precision patterning method for a perovskite film. The difference between this comparative example and Example 1 is that in step S3, the laser used is a femtosecond laser with a wavelength of 450nm, and the other components and preparation methods are the same as those in Example 1.
[0114] Fig.13 A bright field microscope image of the perovskite film prepared in Comparative Example 2 is shown.
[0115] Depend on Fig.13 It can be seen that the perovskite film cannot be patterned using a 450nm femtosecond laser, because perovskite does not undergo nonlinear multiphoton absorption at this wavelength, making it impossible to ablate and remove the perovskite film to obtain a micropattern.
[0116] Comparative Example 3
[0117] A high-precision patterning method for a perovskite film, the difference between this comparative example and Example 1 is that in step S1, no polymer is added, and the other components and preparation methods are the same as those in Example 1. Due to the lack of polymer wrapping and the low concentration of precursor ions, the fluorescence effect of the prepared perovskite film is extremely weak and quenched quickly.
[0118] Comparative Example 4
[0119] A high-precision patterning method for a perovskite film, the difference between this comparative example and Example 1 is that in step S1, the amount of polymer added is 0.25g, and the other components and preparation methods are the same as those in Example 1. Because the mass of the polymer is halved, the film thickness is reduced, and the wrapping effect on the perovskite is weakened, the fluorescence effect and stability of the prepared film are not good, and the fluorescence disappears after being placed for 7 days.
[0120] Application Example 1
[0121] The high-precision patterning method of the perovskite film proposed in the present invention is applied to anti-counterfeiting.
[0122] The preparation method, raw materials and raw material dosage of the perovskite film in this application example are the same as those in Example 1. The femtosecond laser direct writing patterning method of the present invention is used to design and produce micro quick response codes (QR codes) suitable for various information storage scenarios. Based on the simplicity of the production and decoding procedures of the present invention, coupled with the customizable patterning function, the application potential of the present invention is demonstrated - users only need to use a UV light source and a portable microscope that are available everywhere to complete the decryption and identification of information without expensive equipment and professional training.
[0123] Fig.14 The fluorescence image of the patterned micro quick response code (QR code) of Application Example 1 under ultraviolet excitation is shown.
[0124] Application Example 2
[0125] The high-precision patterning method of the perovskite film proposed in the present invention is applied to optical encryption.
[0126] The preparation method, raw materials and raw material dosage of the perovskite film in this application example are the same as those in Example 1. The micro "SCNU" information is encrypted on the perovskite film by using the femtosecond laser direct writing patterning method of the present invention in combination with the standard binary 7-bit ASCII code.
[0127] The details are as follows: The present invention patterns 20×20 μm on the perovskite film 2The solid fluorescent squares and hollow fluorescent squares correspond to the standard binary 7-bit ASCII codes encoded as "1" and "0", respectively. The capital letters "S", "C", "N" and "U" can be translated into "1010011", "1000011", "1001110" and "1010101", respectively. Four rows of 28 fluorescent squares were written on the perovskite film using the patterning method of the present invention, which can be translated into "SCNU" information under fluorescence and microscope modes, demonstrating a simple new method for information storage and encryption. Based on its micro size and high precision characteristics, while retaining visual readability, the risk of counterfeiting is greatly reduced.
[0128] Fig.15 A schematic diagram showing the use of a smart phone, a portable ultraviolet lamp and a microscope to obtain the fluorescent micro-rapid response code and ACSII encrypted coding information in Application Examples 1 and 2 of the present invention.
[0129] Fig.16 The fluorescence image of the patterned binary 7-bit ASCII code of Application Example 2 under ultraviolet excitation is shown.
[0130] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0131] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A high-precision patterning method for a perovskite film, characterized in that: The high-precision patterning method of the perovskite film comprises the following steps: S1, adding a polymer and a perovskite precursor into a solvent, heating and stirring, to obtain a perovskite precursor solution; S2, coating the perovskite precursor solution on a substrate to obtain a perovskite precursor film; S3, annealing the perovskite precursor film to obtain a perovskite film; S4, processing the perovskite film using a femtosecond laser direct writing technique to obtain a high-precision patterned perovskite film; in, The perovskite is a nanocrystalline perovskite; In the perovskite film, the mass fraction of the polymer is 70-90%; The wavelength of the femtosecond laser is 700-1080nm; In the light spot formed by the femtosecond laser, the energy of the femtosecond laser presents a Gaussian distribution curve from the center to the periphery of the light spot, the peak energy of the Gaussian distribution curve reaches 200mW, and the energy decreases from the middle to both sides of the Gaussian distribution curve.
2. The high-precision patterning method of the perovskite thin film according to claim 1, characterized in that: The pulse width of the femtosecond laser is 50-200fs.
3. The high-precision patterning method of the perovskite thin film according to claim 1, characterized in that: The power of the femtosecond laser is 0.1-200 mW.
4. The high-precision patterning method of the perovskite thin film according to claim 1, characterized in that: The spot diameter of the femtosecond laser is 0.5-50 μm.
5. The high-precision patterning method of perovskite thin film according to claim 1, characterized in that: The polymer is selected from one or more of polyvinylidene fluoride, polymethyl methacrylate, polyvinyl acetate, cellulose acetate, polysulfone, polyamide, polyimide, polycarbonate, polystyrene, polyvinyl chloride, polyvinyl alcohol, ABS plastic or polyacrylonitrile.
6. The high-precision patterning method of perovskite thin film according to claim 1, characterized in that: In the perovskite film, the molecular formula of perovskite is ABX3; in, A is selected from Cs + 、CH3NH 3+ or CH5N 2+ One or more of; B is selected from one or more of In, Ag, Al, Ti, Ge, Sn, Pb, Sb, Bi, Cu or Mn; X is selected from Cl - Br - or I - One or more of .
7. The high-precision patterning method of a perovskite thin film according to claim 1, characterized in that: The thermal conductivity of the perovskite is 0.4-10 W / mK; the thermal conductivity of the polymer is 0.1-0.5 W / mK.
8. The high-precision patterning method of a perovskite thin film according to claim 1, characterized in that: In step S1, the heating temperature is 50-90°C; and the stirring time is 1-5h.
9. The high-precision patterning method of a perovskite thin film according to claim 1, characterized in that: In step S3, the annealing temperature is 60-90° C. and the time is 10-30 min.
10. Application of the high-precision patterning method of the perovskite film according to any one of claims 1 to 9 in the fields of high-resolution display, anti-counterfeiting or encryption.
Citation Information
Patent Citations
Two-dimensional nanosheet-polymer flexible composite film and preparation method thereof
CN109762278A
Method for using femtosecond laser for perovskite crystallization for making patterned circuit microstructure
CN109940278A
Full-color fluorescent film patterning method based on laser transfer printing
CN116100972A
Perovskite single crystal film based on LIPSS and preparation method and application thereof
CN116367679A
Cited By
Luminescent solar concentrator with photovoltaic and dimming functions and preparation method thereof
CN121038558A
Laser-induced dehydration phase change perovskite fluorescent patterning device and method
CN122514181A
Full-laser reversible CsPbI3 perovskite thin film fluorescence patterning method
CN122644786A
